Effect of Glyphosate and 2,4-D Herbicides and Bacterial Inoculation on Soil Properties, Growth, and Yield of Maize (Zea mays L.) - Zainab M. Alabadi; Alaa E. Hasan (Journal of Tropical Crop Science, 2026)
Weed-control using herbicides can inhibit weed growth but can also affect soil properties and soil microbial activity, ultimately impacting plant growth and productivity. A field experiment was carried out in Najaf Governorate within the Agricultural Research Station at the University of Kufa during the autumn season of 2024-2025 in a sandy-loam soil to study the effect of glyphosate and 2,4-D herbicides and bacterial inoculation on some soil characteristics, growth, and yield of yellow corn (Zea mays L.). The experiment was conducted using a randomized complete block design with two factors: herbicides at three concentrations (half the recommended, full recommendation, and double the recommended) and bacterial inoculation. The results showed that the interaction treatment between bacterial inoculation (A. chroococcum) and the use of glyphosate at the full recommended concentration, as well as the control treatment, achieved the highest values in the studied characteristics. The highest concentration of available nitrogen in the soil reached 35.67 mg N/kg soil, and available phosphorus reached 26.67 mg P/kg soil. In contrast, the degree of soil reaction remained within the appropriate limits for plant growth. The electrical conductivity decreased to 1.22 dS/m. Soil bacterial counts also increased to 37.00 × 10⁶ CFU/g dry soil, which was reflected in an improvement in total yield to 15.57 mg/ha.